Agrochemicals and sustainable agriculture - Roy, N. K. (New Delhi : APC Publications, 1996)
With reference to Indian context.
Includes bibliographical references.
Keywords: Pesticides -- India; Fertilizers -- India; Sustainable agriculture -- India